2020
DOI: 10.1088/1757-899x/711/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

Experimental research on explosion resistance of masonry structures reinforced with modified polyurea elastomer

Abstract: In order to improve the explosion resistance performance of masonry structures during the terrorist attacks and accidental disasters, clay brick and concrete block walls are reinforced by modified polyurea materials. Explosion resistance tests of these two kinds of masonry wall structures are carried out to analyze the failure modes and anti-explosion effects of reinforced masonry walls under different thickness and reinforcement modes. The results show that modified polyurea elastomer not only has good sprayi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…It was found that the wall reinforced by fiber-reinforced polymer and a polyurea coating can maintain better integrity and can coat the wall fragments and debris in the structure to reduce debris splash. Further study showed that the blast mitigation effect when both side walls were polyurea-coated was better than that of a single polyurea-coated side wall [ 5 , 6 ], and for the one-sided coating wall, coating polyurea on the interior face of walls can better cover the wall debris after explosion than the blast-facing side, and with the increase in the thickness of polyurea coating, the blast mitigation effect of the wall was significantly enhanced [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the wall reinforced by fiber-reinforced polymer and a polyurea coating can maintain better integrity and can coat the wall fragments and debris in the structure to reduce debris splash. Further study showed that the blast mitigation effect when both side walls were polyurea-coated was better than that of a single polyurea-coated side wall [ 5 , 6 ], and for the one-sided coating wall, coating polyurea on the interior face of walls can better cover the wall debris after explosion than the blast-facing side, and with the increase in the thickness of polyurea coating, the blast mitigation effect of the wall was significantly enhanced [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%